Tracking Sustainable Mobility : A New Way to Assess Transport Sector Performance to 2030 and Beyond - Alam, Muneeza (World Bank, Washington, DC, 2018)
In 2015, the world embraced the 17 Sustainable Development Goals (SDGs) for 2030, and agreed on a framework of targets and indicators for tracking progress across multiple economic sectors. Because of the cross-cutting nature of the transport sector, several transport-related targets and indicators are reflected in the SDGs. But in contrast to the health, education, water, and energy sectors, there is no single SDG dedicated exclusively to transport. The sector is also scant in direct targets, indicators, and direct data collection. To address this, the Sustainable Mobility for All (SuM4All) initiative—a multi-stakeholder partnership acting collectively to help transform the transport sector—has developed a Global Tracking Framework (GTF) for transport, complementing the targets and indicators in the SDGs. This Global Tracking Framework is featured in the GlobalMobility Report which provides the first-ever assessment of all modes of transport across theglobe. The framework will provide crucial information and tools to inform transport policy and investment decisions, and provide a baseline for measuring progress toward sustainable mobility.